Performing Everyday Maternal Practice: Activist Structures in Creative Work. Issue 2 (15th December 2016) - Marchevska, Elena
There is a gradual, yet sustained increase in creative practices, which explore maternal everyday experience in various mediums and formats. In this article, I am focusing on a contemporary trend of innovative performative strategies explored by creative practitioners in order to stage the spheres of maternal invisibility. This trend is in a intergenerational dialogue with artwork created almost four decades ago, as an early response to female objectification by art institutions. Current artistic consciousness-raising maternal projects similarly share personal experiences within a more public space, to provide focus on personal and social injustice.